2020
DOI: 10.1101/2020.10.23.352088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking pre-mRNA maturation across subcellular compartments identifies developmental gene regulation through intron retention and nuclear anchoring

Abstract: To globally assess the distribution and processing of gene transcripts across subcellular compartments, we developed extensive RNA-seq datasets of both polyA+ and total RNA from chromatin, nucleoplasm and cytoplasm of mouse ESC, neuronal progenitors, and neurons. We identified protein-coding genes whose polyadenylated transcripts were more abundant in chromatin than cytoplasm. We defined introns exhibiting cotranscriptional splicing, complete intron retention in cytoplasmic RNA, and many introns retained in nu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 83 publications
1
28
0
Order By: Relevance
“…We next sought to identify the factors responsible for mediating the post-transcriptional consequences of PRMT inhibition. Previous reports have highlighted that delayed cotranscriptional splicing leads to chromatin retention of poly(A) transcripts (Brody et al 2011;Pandya-Jones et al 2013;Yeom et al 2021). Therefore, we analyzed differences in proteins bound to chromatin-associated poly(A) RNA.…”
Section: Prmts Regulate the Binding Of Rna Processing Factors To Chromatin-associated Poly(a) Rnamentioning
confidence: 99%
“…We next sought to identify the factors responsible for mediating the post-transcriptional consequences of PRMT inhibition. Previous reports have highlighted that delayed cotranscriptional splicing leads to chromatin retention of poly(A) transcripts (Brody et al 2011;Pandya-Jones et al 2013;Yeom et al 2021). Therefore, we analyzed differences in proteins bound to chromatin-associated poly(A) RNA.…”
Section: Prmts Regulate the Binding Of Rna Processing Factors To Chromatin-associated Poly(a) Rnamentioning
confidence: 99%
“…To test this hypothesis, we examined whether the nuclear IRs harbor specific sequence properties. Nuclear retained introns exhibit weak 5' and 3' splice sites compared to canonically spliced introns -a general property of IRs (Boutz et al, 2015;Braunschweig et al, 2014;Mauger et al, 2016;Ullrich and Guigó, 2020;Yeom et al, 2021). However, the splice site strength of stable nuclear retained introns is indistinguishable from the one of cytosolic retained introns (Figure 1E and F).…”
Section: Stable Nuclear Irs Share Features With Canonical Spliced Intronsmentioning
confidence: 94%
“…Furthermore, active nuclear retention of mRNAs is emerging as a novel form of posttranscriptional gene regulation. Notably, nuclear retention of RNAs can be regulated through long-lasting processes such as neuronal differentiation (Yeom et al, 2021). Also, candidate gene approaches in several systems revealed that some stored and nuclear transcripts can be released into the cytosol upon acute signals, thereby rapidly increasing mRNAs' availability for translation (Boutz et al, 2015;Mauger et al, 2016;Naro et al, 2017;Ninomiya et al, 2011;Prasanth et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations